The New Development Economics: We Shall Experiment, but How Shall We Learn? - and Rodrik, Dani (SSRN, 2008)
Development economics is split between macro-development economists - who focus on economic growth, international trade, and fiscal/macro policies - and micro-development economists - who study microfinance, education, health, and other social programs. Recently there has been substantial convergence in the policy mindset exhibited by micro evaluation enthusiasts, on the one hand, and growth diagnosticians, on the other. At the same time, the randomized evaluation revolution has led to an accentuation of the methodological divergence between the two camps. Overcoming the split requires changes on both sides. Macrodevelopment economists need to recognize the distinct advantages of the experimental approach and adopt the policy mindset of the randomized evaluation enthusiasts. Micro-development economists, for their part, have to recognize that the utility of randomized evaluations is restricted by the narrow and limited scope of their application. As the Chinese example illustrates, extending the experimental mindset to the domain of economy-wide reforms is not just possible, it has already been practiced with resounding success in the most important development experience of our generation.
Keywords: Economics; Finance; Health Care; International Development; International Economics; International Trade; Macroeconomics; Microeconomics; Social Policy; Welfare